Batas Toleransi Laju Alir dari Mikroalga (Nannochloropsis Oculata dan Botrycoccus Braunii) dengan Konsentrasi CO2 Konstan dalam Fotobioreaktor - Agus Rivaldy Kurnia; Sakha Abdussalam; Elida Purba (Balitbangda Provinsi Lampung, 2017)
This research was conducted on the absorbtion of CO2 in air by utilizing microalgae as CO2 absorbent agent. The research used two types of microalga Nannochloropsis oculata and Botrycoccus braunii. The purpose of this study was to obtain a flow rate tolerance limit with constant CO2concentrationin aphotobioreactor and to compare the two microalgaefollowingCO2 absorption data and biomass growth. The research used variation of feed flow rate of 1, 1.5, and 2 l/min with fixed CO2concentration at 33 %. The study used culture volume of 4 l (1 l of microalgae and 3 l of sea water) for 6 days. The results showed that the optimum flow rate for Nannochloropsis oculata was at a flow rate of 2 l/min to result in an absorption percentage of 71.54 %, while the optimum flow rate for Botrycoccus braunii is 1 l/min to result in an absorption percentage of 70.16 %.The dataindicated thatthe maximum point of tolerance of feed flow rate for Botrycoccus braunii is 1 l/min with 33 % CO2 concentration, while for Nannochloropsis oculata did not achieve maximum flow rate tolerance because at the variation of 2 l/min flow rate with CO2 concentration of 33 % it still had a good ability in the process of CO2 biofixation. It is therefore necessary to provide a greater variation in flow rates for Nannochloropsis oculata microalgae to obtain a point of flow rate tolerance.